Perceived Wealth, Cognitive Sophistication and Behavioral Inattention - Tiziana Assenza; Alberto Cardaci; Domenico Delli Gatti (Center for Economic Studies and ifo Institute (CESifo), 2019)
By means of a laboratory experiment, we show that, contrary to standard consumer theory, financially equivalent balance sheet profiles may be perceived as non fungible in a controlled frictionless environment with no probabilistic attributes. A large majority of subjects indeed have a bias in the perception of wealth, such that balance sheet composition matters: for a given net worth with values of assets and debt that are financially certain and risk-free, a greater asset-debt ratio implies greater perceived wealth. The predominance of this bias is explained by low cognitive sophistication and great inattention. Moreover, biased subjects are less patient, less debt averse, more likely to increase spending out of unexpected gains and report greater propensities to consume. A standard optimal consumption choice model, enriched with a rational but inattentive agent à la Gabaix (2014, 2019), aligns our key experimental findings.
Keywords: C91; D91; G41; G51; 330; perceived wealth; cognitive sophistication; behavioral inattention; laboratory experiment; household debt; consumption